Mitigating Disruption from Global Increment Price of Material in Car Manufacture Industry: Analysis of Supply Chain Business Process Analysis, and Process Re-Engineering - Oky Dzulqarnain; Nurmala Nurmala (Management Analysis Journal, 2023)
The existence of raw materials is crucial for Car Manufacturers and their suppliers in the production process. The Covid-19 pandemic has affected the global economy and led to a global increase in material prices. This has had a significant impact on production costs and the competitiveness of companies. In order to maintain competitiveness, companies need to implement the appropriate supply chain management strategies. This research utilizes the SCOR Framework and BPMN to evaluate and enhance the supply chain operations performance in Car Manufacturing companies. The purpose of this study is to evaluate the current supply chain performance and provide recommendations for the appropriate supply chain business processes in addressing the phenomenon of global material price increases. This research is conducted through qualitative and exploratory quantitative methods using the SCOR framework and BPMN. The research findings indicate that the supply chain performance is still lacking in the procurement area. Therefore, business process re-engineering needs to be conducted by transforming the current supplier-led raw material purchasing into self-purchase by the Car Manufacturer. The recommendation for the new business process is for the Car Manufacturer to directly purchase the raw materials for the supplier's needs, thereby eliminating the handling fee charged by the supplier.